Minimum rainbow H-decompositions of graphs. (June 2018) - Özkahya, Lale; Person, Yury
Abstract: Given graphs G and H, we consider the problem of decomposing a properly edge-colored graph G into few parts consisting of rainbow copies of H and single edges. We establish a close relation to the previously studied problem of minimum H -decompositions, where an edge coloring does not matter and one is merely interested in decomposing graphs into copies of H and single edges.